Jestem Bogiem w ciele. Jestem uczuciem w transie. Jestem człowiekiem w transie. Literacki i taneczny zapis choroby Wacława Niżyńskiego - Waligórska-Olejniczak, Beata (Uniwersytet Opolski, 2010)
Vaclav Nijinsky’s drawings, which were created during the years 1918-1919 constitute the artistic expression of the illness of the dancing genius, they tell us the story of the psychotic experience of the Russian-Polish ballet master. The fear is merged in them with suspicion and the feeling of insecurity, derived from hallucinations and paranoid perception of the reality. The strangeness and gloom of the drawings is tiring for the viewer as well as the repetitious use of certain demoniac figures and patterns. The artistic, kinetic and literary record of Nijinsky’s psychosis give unlimited opportunities of scientific penetration of his emotions and experiences, which accompanied the years spent in the USA, London and the period of internment in Budapest. The aforementioned sources motive also to consider the question concerning the relationship between the total engagement in the dance and the artist’s illness.
I'm an incarnated God. I'm a feeling in a trance. I'm a human being in a trance. The literary and kinetic record of Vaclav Nijinsky's illness
Keywords: Niżyński; Nijinsky; schizofrenia; szaleństwo; taniec; dance; balet; ballet; choroba psychiczna; dziennik; diary